2022
DOI: 10.1186/s40795-022-00499-7
|View full text |Cite
|
Sign up to set email alerts
|

Missed opportunities to improve food security for pregnant people: a qualitative study of prenatal care settings in Northern New England during the COVID-19 pandemic

Abstract: Background Food insecurity during pregnancy has important implications for maternal and newborn health. There is increasing commitment to screening for social needs within health care settings. However, little is known about current screening processes or the capacity for prenatal care clinics to address food insecurity among their patients. We aimed to assess barriers and facilitators prenatal care clinics face in addressing food insecurity among pregnant people and to identify opportunities t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…Studies have shown that interventions involving referrals from practices to community food resources can increase use of food resources among patients. 12 In our team’s qualitative work on FI in prenatal care settings, 22 clinics primarily addressed FI through internal referrals to clinic-based staff, such as a dedicated resource specialist, who could then refer to community resources. Practice staff discussed the importance of strong relationships between the clinic and the community organizations, and felt that better coordination between clinics and various community resources was needed to address FI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that interventions involving referrals from practices to community food resources can increase use of food resources among patients. 12 In our team’s qualitative work on FI in prenatal care settings, 22 clinics primarily addressed FI through internal referrals to clinic-based staff, such as a dedicated resource specialist, who could then refer to community resources. Practice staff discussed the importance of strong relationships between the clinic and the community organizations, and felt that better coordination between clinics and various community resources was needed to address FI.…”
Section: Discussionmentioning
confidence: 99%
“…Practice staff discussed the importance of strong relationships between the clinic and the community organizations, and felt that better coordination between clinics and various community resources was needed to address FI. 22 Health care organizations that screen for FI and connect patients to food resources partner with a variety of community organizations, most commonly food banks. 23 This supports our findings, which suggest that collaboration between practices and community food programs is important for addressing FI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the low quality of the foods consumed, the perinatal outcomes got worse [ 101 ]. Interestingly, researchers in Northern New England have proposed a model to identify and address questionable food choices among pregnant women during the pandemic period, highlighting the need for specific food programs [ 107 ]. Erol et al discussed that vit E and Afamin are significant predictors of adverse perinatal outcomes in COVID-19 infected women.…”
Section: Nutrition In Pregnancy During Covid-19 Infectionmentioning
confidence: 99%
“…Short screening measures are limited in that they do not allow for the assessment of the severity of food insecurity, however, they are more appropriate for busy clinical settings and take into consideration barriers including time constraints and increased workloads experienced by clinicians, while still being able to determine food secure status [ 55 ]. While it is clear that clinicians consider food insecurity screening as an important component of antenatal healthcare [ 16 , 56 ], there are a variety of barriers that may prevent them from asking their patients about their household food security. This includes a lack of guidelines, uncertainty surrounding responsibility for screening, inadequate clinical knowledge and training, and time constraints [ 16 , 56 ].…”
Section: Institutional Level Solutionsmentioning
confidence: 99%
“…Recent research has found that while health care providers in one Australian antenatal setting were aware of the importance of maternal nutrition for the short- and long-term health of both the mother and baby, they were uncertain how to broach issues surrounding food insecurity, and when they do, they have few strategies to assist the hungry or food insecure parent [ 16 ]. Assisting clinicians when they encounter women who are experiencing hunger or food insecurity during their pregnancy will increase the opportunity for better birth and pregnancy outcomes [ 17 ]. Clinical practice guidelines are often used in these situations to provide guidance for clinicians when dealing with patient concerns, however, as yet there are no such Australian guidelines or advice that assist antenatal management of women who are food insecure both during and following pregnancy.…”
Section: Introductionmentioning
confidence: 99%